2008
DOI: 10.1137/070696076
|View full text |Cite
|
Sign up to set email alerts
|

Direct Elastic Imaging of a Small Inclusion

Abstract: Abstract. In this paper we consider the problem of locating a small three-dimensional elastic inclusion, using arrays of elastic source transmitters and receivers. This procedure yields the multistatic response matrix that is characteristic of the elastic inclusion. We show how the eigenvalue structure of this matrix can be employed within the framework of a noniterative method of MUSIC (multiple signal classification) type in order to retrieve the elastic inclusion. We illustrate our reconstruction procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…In 3d, the elastic moment tensor M for a unit ball-inclusion x has also been computed in [11]. The topological derivative (4.5) for a ball-inclusion is:…”
Section: Resultsmentioning
confidence: 99%
“…In 3d, the elastic moment tensor M for a unit ball-inclusion x has also been computed in [11]. The topological derivative (4.5) for a ball-inclusion is:…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the Lamé system, we cite the works , , , where, as we just mentioned, the asymptotics are given in terms of the size of the scatterers only. In these works, the authors considered transmission problems and showed that the corresponding moment tensors are in general anisotropic.…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%
“…The concept of topological sensitivity (TS), since its inception in the context of structural shape optimization, [9,10] has been generalized and applied to deal with inverse scattering problems in acoustics, [7,[11][12][13][14][15][16][17] electromagnetism, [18][19][20][21][22][23] and elastodynamics. [24][25][26][27][28][29][30][31][32][33] In the reconstruction approach, the TS indicator function is defined as the sensitivity of a given cost functional (that would commonly be used as a platform for non-linear minimization) with respect to the nucleation of an infinitesimal obstacle at a prescribed sampling point in the reference (background) medium. Accordingly, the support of hidden obstacles is exposed through the spatial distribution of topological sensitivity, namely the regions where TS attains pronounced negative values.…”
Section: Introductionmentioning
confidence: 99%